High Molecular-Weight Thermoplastic Polymerization of Kraft Lignin Macromers with Diisocyanate - Le Dai Duong; Gi-Yong Nam; Joon-Suk Oh; In-Kyung Park; Nguyen Dang Luong; Ho-Kyu Yoon; Seong-Hoon Lee; Youngkwan Lee; Ju-Ho Yun; Chong-Gu Lee; Suk-Ho Hwang; Jae-Do Nam (BioResources, 2014)
A high molecular-weight thermoplastic lignin-based polymer was successfully synthesized by adjusting the degree of polymerization while inducing linear growth of lignin macromers via methylene diphenyldiisocyanate. The thermoplastic lignin-urethane polymer was desirably achieved in a narrow range of reaction conditions of 2.5 to 3.5 h at 80 oC in this study, and the molecular weight of the resulting lignin-based polyurethanes (LigPU) reached as high as 912,000 g/mole, which is far above any reported values of lignin-based polymer derivatives. The thermal stability of LigPU was greatly improved by the urethane polymerization, giving the initial degradation temperature (T2%) at 204 °C, which should be compared with T2% = 104 °C of the pristine lignin. This was due to the fact that the OH groups in the lignin macromers, having low bond-dissociation energy, were replaced by the urethane bonds. In dielectric analysis, the synthesized LigPU exhibited a softening transition at 175 °C corresponding to a combinatorial dual process of the dry Tg,dry of the lignin macromers and the softening of methylenediphenyl urethane chains. This work clearly demonstrated that a high molecular weight of thermoplastic LigPU could be desirably synthesized, broadening the lignin application for value added and eco-friendly products through common melt processes of polymer blend or composites.